Clinical study on postpartum eclampsia - J., Madhu; Shankar, Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Eclampsia constitutes one of the deadly triad along with malnutrition and anemia which authors encounter in the present tertiary hospital Karnataka Institute of Medical Sciences, Hubli. This study was done to study the epidemiological factors associated with postpartum eclampsia, correlation with neuroimaging and the maternal outcome. The objective of the present study was retrospective study of postpartum eclampsia over a period of 22 months. Methods: A retrospective study conducted over a period 22 months from June 2015 to March 2017 in a tertiary care hospital, Karnataka Institute of Medical Sciences, Hubli. Case records of all postpartum eclampsia patients admitted during the period were analyzed. Results: This study showed that incidence of postpartum eclampsia in our hospital was 1.4%. It is more common in age group of 20-25 years, more common in primipara (67.24%), commonest mode of delivery was vaginal route (86.2%), the occurrence of convulsion was more common within 24hrs after delivery. Most common CT scan finding was normal study (51.72%) followed by cerebral infarct (15.5%), cerebral edema (13.72%), PRES (10.34%). There were no cases of maternal mortality due to postpartum eclampsia during study period. Conclusions: Eclampsia still remains a major cause of maternal morbidity, CT scan of brain gives valuable intracerebral information, and aids in a better management.